A Traditional Journey in Contemporary Times: The Pilgrimage of Mehmet Barut - İbrahim Özen (Religions, 2025)
In Turkish literature, hajj travelogues have been written since the 13th century, conveying Muslims’ experiences during the pilgrimage and explaining how to perform hajj. With the development and widespread use of the modern means of transportation in Türkiye from the 1940s onward, the pilgrims increasingly started to travel by air to avoid the hardships and duration of long journeys. However, this shift led to a decrease in visits to historical places along the traditional pilgrimage route from Türkiye to Mecca and Medina, consequently changing the content and nature of Hajj narratives. In spite of these changes, Mehmet Barut, a mufti (cleric), offered a unique response through his travelogue Hicaz Yolları [Hijaz Roads], which can be seen as a reaction to the rise in modern means of transportation. In 1965, Barut began his hajj journey from Tokat, within the border of the Republic of Türkiye, and travelled to Mecca and Medina by bus. Along the way, he visited Ankara, Konya, Tarsus, Iskenderun, Reyhanlı, Aleppo, Damascus, Jerusalem, Halilurrahman, Amman, Tabuk, Khaybar, and Medina before finally reaching Mecca. Barut’s travelogue is a contemporary non-fiction work, yet it was written in classical Turkish. In choosing to follow the historical pilgrimage route—established during the Ottoman period and beginning in Anatolia—Barut sought to revive and preserve the spiritual and cultural destinations and hajj journeys. His travelogue not only demonstrates his own travel experiences, but also reflects examples from the travelogue menazil-i hajj, offering insights into the historical significance of the cities and stopovers along the route. This study examines Hicaz Yolları from two key perspectives. First, it compares Barut’s chosen route with the historical Ottoman hajj route, highlighting key service areas and stopovers. Second, it explores the literary value of Barut’s work and its significance in contemporary Turkish literature. Ultimately, this study reveals that Barut’s travelogue not only kept the memory of traditional hajj pilgrimages alive, but also revived a fading tradition in an era dominated by modern means of transportation.